2017
DOI: 10.1186/s13037-017-0128-y
|View full text |Cite
|
Sign up to set email alerts
|

Empty polyetheretherketone (PEEK) cages in anterior cervical diskectomy and fusion (ACDF) show slow radiographic fusion that reduces clinical improvement: results from the prospective multicenter “PIERCE-PEEK” study

Abstract: BackgroundAnterior cervical diskectomy and fusion (ACDF) is a well-established surgical treatment for radiculopathy and myelopathy. Previous studies showed that empty PEEK cages have lower radiographic fusion rates, but the clinical relevance remains unclear. This paper’s aim is to provide high-quality evidence on the outcomes of ACDF with empty PEEK cages and on the relevance of radiographic fusion for clinical outcomes.MethodsThis large prospective multicenter clinical trial performed single-level ACDF with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…We required minimum radiographic follow-up of 2 years for inclusion in our review ( Table 3). The 1 high-quality study excluded because of a lack of 2-year radiographic follow-up was the PIERCE-PEEK Study (Prospective International Multicenter Evaluation of Radiological and Clinical Effects of Stand-Alone PEEK Intervertebral Spacers for ACDF) by Suess et al 9 The authors followed a cohort of 356 patients who underwent ACDF with PEEK interbody devices without any osteopromotive fillers and without additional anterior instrumentation. Complete radiographic fusion occurred for 43% of patients at 6 months, 73% of patients at 12 months, and 83% of patients at 18 months.…”
Section: Discussionmentioning
confidence: 99%
“…We required minimum radiographic follow-up of 2 years for inclusion in our review ( Table 3). The 1 high-quality study excluded because of a lack of 2-year radiographic follow-up was the PIERCE-PEEK Study (Prospective International Multicenter Evaluation of Radiological and Clinical Effects of Stand-Alone PEEK Intervertebral Spacers for ACDF) by Suess et al 9 The authors followed a cohort of 356 patients who underwent ACDF with PEEK interbody devices without any osteopromotive fillers and without additional anterior instrumentation. Complete radiographic fusion occurred for 43% of patients at 6 months, 73% of patients at 12 months, and 83% of patients at 18 months.…”
Section: Discussionmentioning
confidence: 99%
“…The authors note the low fusion rates of empty PEEK cages, but stated that the lack of fusion did not affect clinical outcomes. Similarly, Suess et al evaluated the clinical and radiographic outcomes of 292 patients who received empty PEEK cages for single-level ACDF procedures [56]. PEEK demonstrated radiographic fusion in 126 patients (43%) at 6 months, 214 patients (73%) at 12 months, and 241 patients (83%) at 18 months.…”
Section: Figure 6 (A) Structural Interbody Spacer With Cancellous Bomentioning
confidence: 99%
“…1 Post-operative radiographs of a 46-year-old female who underwent anterior cervical discectomy and fusion with PEEK cages filled with bone marrow aspirate. Surgical indication was right arm radiculopathy that failed non-surgical treatment recent prospective multicenter study on 292 patients by Suess et al [18] indicated poor performance of empty standalone PEEK cages. They found that these cages had slow radiographic fusion rates with an 83% complete fusion at 18 months, which translated into poor clinical outcomes.…”
Section: Fusion and Subsidence Ratesmentioning
confidence: 99%
“…A change by 2. Regarding empty PEEK cages, Suess et al [18] reported in an RCT a mean change of 4 (interquartile range 3-6 if fused or 3-4 if not fused) following ACDF at 18 months. The rest of the studies on empty PEEK cages were case series.…”
Section: Visual Analogue Scalementioning
confidence: 99%
See 1 more Smart Citation